MAKING A COMPREHENSIVE ARMS CONTROL AGREEMENT FOR EUROPE IN TIMES OF CRISIS: RATIONALE, STRUCTURE, AND OUTCOMES - Stefanović, Andrej; Kostić Šulejić, Marina (The Policy of National Security, 2024)
The war in Ukraine reflects the culmination of two international crises – one of the European security architecture and the other of strategic stability. This paper aims to examine how these crises influence the feasibility of future arms control in Europe. The authors claim that the current situation is an opportunity for a comprehensive arms control agreement for Europe. They begin by providing a theoretical framework of international crises and explain the current state of the arms control regime. Through a content and discourse analysis, they consider the positions of the main actors in relation to the key elements of future arms control and, based on this, by using a comparative method, consider the possible common ground that would serve as the bedrock for a new European comprehensive arms control regime. The article concludes that by going comprehensive, arms control can provide grounds for trade-offs between the parties, settling most issues of concern in a multi-track process.
Keywords: arms control; international crisis; Europe; war in Ukraine; strategic stability